REVIEW OF THE IMPACT OF VOCABULARY ON CONVERSATIONAL PRACTICE (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. The thesis discusses the need to improve the communication skills of foreign language students. The author analyzes the use of video material in foreign language classes as one of the most effective methods for learning foreign languages. The thesis proves the need to use video material and vocabulary mastery in the classroom.